The Food Movement, Culture, and Religion A Tale of Pigs, Christians, Jews, and Politics - Schorsch, Jonathan (Springer International Publishing, 2018)
This book explores the cultural and religious politics of the contemporary food movement, starting from the example of Jewish foodies, their zeal for pig (forbidden by Jewish law), and their talk about why ignoring traditional precepts around food is desirable. Focusing on the work of Michael Pollan, Jonathan Schorsch questions the modernist, materialist, and rationalist worldview of many foodies and discusses their lack of attention to culture, tradition, and religion. .